Corporate Philanthropy Disclosure of State-Owned Enterprises in Indonesia - Agung Nur Probohudono; Raja Adzrin Raja Ahmad; Indra Kristianto Pambudi; Nur Chayati (Universitas Pasundan, 2020)
Corporate philanthropy is becoming big in businesses and a major strategic issue for firms as they actively aim to be socially responsible organizations. This study aims to measure the extent of corporate philanthropy disclosure (CPD) and the impacts of foreign ownership, managerial ownership, the proportion of independent directors, and company size on CPD in annual reports of state-owned enterprises (SOEs) in Indonesia. The level of CPD in this study was measured using an index adapted from earlier research and regulation. Annual reports of 153 SOEs for 2010–2012 were examined to measure the extent of CPD and investigate its potential determinant factors. Study results indicate that company size has a significant positive effect on CPD and managerial ownership has a moderate effect. In addition, the results also show that the control variable, public company (Perum), has a significant effect on CPD in SOEs in Indonesia. The average CPD rate is only 63.00%, which indicates that CPD has been commonly disclosed in annual reports. The findings regarding corporate philanthropy in annual reports should be a concern to regulatory authorities and standard-setters in Indonesia.